Analysis of the Challenges of Sustainable Organizational Development in a Changing Business Environment - Nurhidayah, Nurhidayah; Wahyuni, Wahyuni (Advances in Management & Financial Reporting, 2026)
Purpose: This study explores organizations' challenges in implementing sustainable development strategies in a rapidly evolving business environment. It examines key barriers, including regulatory constraints, financial limitations, challenges in adopting technology, and organizational resistance, while assessing the roles of leadership, governance, and innovation in fostering sustainability. Research Method: This study uses a Systematic Literature Review (SLR) to synthesize peer-reviewed research on sustainability challenges and strategic responses. The review integrates perspectives from Institutional Theory to understand how external pressures influence corporate sustainability practices. The study also draws on empirical findings from recent literature to provide a structured evaluation of the factors affecting the integration of sustainability. Results and Discussion: The findings highlight that regulatory frameworks and market expectations are the primary drivers of sustainability adoption. However, many organizations struggle to balance short-term financial performance with long-term sustainability investments. The study identifies technological innovation as a key enabler of sustainable practices but notes significant barriers, such as high investment costs and skill gaps. Furthermore, effective leadership and corporate governance are critical in shaping organizational sustainability cultures. Implications: This study offers practical insights for businesses, policymakers, and researchers by emphasizing the need for integrated sustainability strategies that go beyond compliance. It calls for enhanced regulatory alignment, cross-sector collaborations, and investment in digital sustainability solutions to drive long-term resilience. Future research should explore sector-specific sustainability challenges and the effectiveness of leadership models in driving sustainability transformation.